Long-Term DL-3-n-Butylphthalide Treatment Alleviates Cognitive Impairment Correlate With Improving Synaptic Plasticity in SAMP8 Mice - Lv, Chaonan; Ma, Qinying; Han, Bing; Li, Jing; Geng, Yuan; Zhang, Xiaoman; Wang, Mingwei (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is the most prevalent form of dementia worldwide. AD is characterized by mild cognitive impairment at onset, irreversibly progressing with age to severe neurodegeneration and cognitive deficits in the late stages. Unfortunately, no effective treatments exist to prevent or delay the cognitive symptoms of AD. Studies have shown that DL-3-n-butylphthalide (DL-NBP) alleviates cognitive impairment induced by amyloid-β in mice by reducing oxidative stress, inhibiting apoptosis, and decreasing tau phosphorylation. In this study, we examined the effects of DL-NBP administration on cognitive function in the senescence-accelerated mouse prone 8 (SAMP8) model of age-related dementia. DL-NBP treatment for 3 months alleviated cognitive impairment in SAMP8 mice as assessed by performance in the Morris water maze test. Moreover, DL-NBP significantly increased the expression of synaptophysin and postsynaptic density protein 95 in the hippocampus of SAMP8 mice, indicative of a protective effect on hippocampal structural synaptic plasticity. In addition, brain-derived neurotrophic factor/tropomyosin receptor kinase B signaling, previously shown to promote synaptic plasticity, was significantly enhanced by the DL-NBP administration. Our findings suggest that DL-NBP is a potential drug candidate for the treatment of cognitive impairment in AD and may serve as the foundation for further research into the development of AD drugs.